2022
DOI: 10.3390/universe8100495
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of the Heliospheric State and the Solar-Wind/Magnetosphere Coupling in the Era of Weakened Solar Activity

Abstract: Based on the data of the solar wind (SW) measurements of the OMNI database for the period 1976–2019, we investigate the behavior of SW types, as well as plasma and interplanetary magnetic field (IMF) parameters, for 21–24 solar cycles (SCs). Our analysis shows that with the beginning of the period of low solar activity (SC 23), the number of all types of disturbed events in the interplanetary medium decreased, but the proportion of magnetic storms initiated by CIR increased. In addition, a change in the nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, because the CIR driven storms are small in number, we consider only the 196 ICME driven storms for the epoch analysis in this paper. The number of storms, especially CIR‐driven storms, are small compared to previous studies (e.g., Yermolaev et al., 2022) because only the clear storms satisfying four selection criteria are identified. The ICME driven storms could be generated by both magnetic clouds and area of compression in front of them, the sheath (Yermolaev et al., 2014).…”
Section: Discussionmentioning
confidence: 86%
“…However, because the CIR driven storms are small in number, we consider only the 196 ICME driven storms for the epoch analysis in this paper. The number of storms, especially CIR‐driven storms, are small compared to previous studies (e.g., Yermolaev et al., 2022) because only the clear storms satisfying four selection criteria are identified. The ICME driven storms could be generated by both magnetic clouds and area of compression in front of them, the sheath (Yermolaev et al., 2014).…”
Section: Discussionmentioning
confidence: 86%
“…In one of our recent papers [19], we also showed that the time profiles of all SW parameters in all types of large-scale phenomena in SCs 23-24 have a similar shape with the same profiles in SCs 21-22, but located at lower values. In addition, there is a sharp drop in the number of ICMEs in the last two cycles [25,27]. These results indicate a weakening of the solar wind during the Sun's transition from the epoch of high activity in SCs 21-22 to the epoch of low activity in SCs 23-24.…”
Section: Introductionmentioning
confidence: 79%
“…Indeed, having previously smoothed the accumulated hourly data the Dst index and the β parameter from [Kurazhkovskaya et al, 2021] by a running average, we plot Dst(β) for the interval of 168 hrs from storm commencements. This time interval covers the average duration of the storm main phase, which, according to [Yermolaev et al, 2007], is 74 hrs, and the storm recovery phase, which on average lasts for 5-7 days. Figure 4 It can be seen that the trajectory of variation in the Dst index depending on the β parameter in the storm main phase is seen to differ from its trajectory in the recovery phase.…”
Section: Discussionmentioning
confidence: 99%